2014
DOI: 10.1002/mrm.25246
|View full text |Cite
|
Sign up to set email alerts
|

SAR reduction in 7T C‐spine imaging using a “dark modes” transmit array strategy

Abstract: Purpose Local specific absorption rate (SAR) limits many applications of parallel transmit (pTx) in ultra high-field imaging. In this Note, we introduce the use of an array element, which is intentionally inefficient at generating spin excitation (a “dark mode”) to attempt a partial cancellation of the electric field from those elements that do generate excitation. We show that adding dipole elements oriented orthogonal to their conventional orientation to a linear array of conventional loop elements can lower… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 16 publications
0
25
0
Order By: Relevance
“…from ref. , where dipole antennas are employed in conjunction with loops. Although this design is unconventional, each element in this array is driven independently, and it may be used in exactly the same way as any other PTx array using any of the optimization methods outlined previously.…”
Section: Sarmentioning
confidence: 99%
See 1 more Smart Citation
“…from ref. , where dipole antennas are employed in conjunction with loops. Although this design is unconventional, each element in this array is driven independently, and it may be used in exactly the same way as any other PTx array using any of the optimization methods outlined previously.…”
Section: Sarmentioning
confidence: 99%
“…Although this design is unconventional, each element in this array is driven independently, and it may be used in exactly the same way as any other PTx array using any of the optimization methods outlined previously. It has been demonstrated that potentially large reductions in local SAR can be achieved. Although these approaches are still in their infancy, previous theoretical studies into optimal current distributions suggest that there are significant benefits yet to be obtained .…”
Section: Sarmentioning
confidence: 99%
“…On the other hand, all the elements of the partially orthogonal array have sensitivity to the signal, at least partially. This is also distinctive from previous approaches that employed entire elements virtually insensitive to the signal used to reduce E-fields 19 20 .…”
Section: Discussionmentioning
confidence: 88%
“…An increased number of transmit elements, either normalB1+‐producing loops or loops combined with dipole elements , can potentially reduce peak local SAR involved in producing a given normalB1+ distribution. Compared with a simulated one‐panel transmit array, our two‐panel design indeed deposited a lower maximum 10‐gram averaged SAR while producing greater normalB1+ in the center of the neck and the same normalB1+ field in the center of the lower part of the head.…”
Section: Discussionmentioning
confidence: 99%